(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Recently, a lot of studies have been interested in recognizing and detection of emotions in people with autism. The main goal of this paper is to survey different studies which have been concerned emotional state of people with autism. The survey includes two parts, first one focused on studies which use facial expressions to recognize and detect emotions. As facial expressions are considered the affective and important techniques which is used to express different patterns of emotions. Second parts of this study, focuses on different technical methods like machine learning, deep learning and other algorithms that are employed to analyze and determine the facial behaviors of people with autism. To find the optimal solution, a comparison of current emotion-detecting systems is investigated in this paper.